Peramalan Beban Jangka Panjang Sistem Kelistrikan Kota Palu Menggunakan Metode K Logika Fuzzy - Masarrang, Maryantho; Yudaningtyas, Erni; Naba, Agus (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Brawijaya, 2015)
Long-term load forecasting is intended to estimate the electrical load on an annual time period. It has an important role in the real control and security functions of an energy management system. This study is focused on designing long-term load forecasting in Palu electrical systems by using mamdani fuzzy logic method. The process of long term load forecasting is done by providings inputs; the number of customers, PDRB, and the power used for residences, businesses and public load at the previous year into the fuzzy logic system so that it is produced an output: the power used for the next year. The shows that mamdani fuzzy logic provide high level accuracy of forecasting and very small value of MSE.Index Terms:- fuzzy logic, MSE value, number of consumers, PDRB, the power used